Determining a Fire Potential Map Based on Stand Age, Stand Closure and Tree Species, Using Satellite Imagery (Kastamonu Central Forest Directorate Sample) - Aricak, Burak; Kucuk, Omer; Enez, Korhan (University of Zagreb, Faculty of Forestry, 2014)
Becoming successful in fighting forest fires is not only a matter of taking the required measures into consideration and efficiently and economically using the resources, but also employing the cutting edge science and technology in every aspect of the process. Determining the potential fire prone regions within forest stands, plays an important role in the success rate of forest fire prevention and firefighting. Various techniques are used in the determination of fire potential; especially high resolution satellite imagery can provide very sensitive and detailed information regarding the conditions of regional topography and fuel material (fuel) accumulation. Fuel material models have long been effectively used in fire management, fire behavioral estimates and determination of fire danger risks. Additionally, fuel material maps, prepared based on fuel material features, can help in the determination of fire potential. Fire potential maps include fuel material types and their distribution in the field. In this particular study, an October, 2011 dated »GeoEye« image, encompassing 24 320 ha of Kastamonu Central Forest Directorate area, 15 685 ha of which is forested, was used. The image was classified based on fuel material features, such as tree species, mixture, crown closure, age classes, etc. Acreages and distributions of the potential fire prone areas were determined, and where these areas were concentrated, possible fire suppressing precautionary methods were discussed. As long as the satellite image acquisition is periodically supplied, fire potential map can be updated depending on fuel material features.
Keywords: remote sensing; Turkey; Forestry; SD1-669.5; GIS; forest fire